Taṭbīq al-Manhaj al-Qā’im litarqiyyah Mahārah al-Kalām liṭalabah al-Ma’had - Zuhriyah, Arina Alfi Aminatuz; Abdur Rohman, Muhamad Asvin; Ana, Sri (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The purpose of this research is (1) to describe the application of the Islamic Teachers College curriculum in improving the speaking skills of first-year experimental students at the Darul Fikri Islamic Boarding School. (2) describe the supporting and inhibiting factors in implementing the Islamic Teachers' College curriculum to improve first-year experimental students' speaking skills at the Darul Fikri Islamic Boarding School, Ponorogo. (3) describe the effect of implementing the Islamic Teachers College curriculum in improving the speaking skills of first-year experimental students at the Darul Fikri Islamic Boarding School, Ponorogo. The research method used is qualitative with a case study approach. Data collection techniques use observation, interviews, and documentation. Data analysis with stages of data reduction, data presentation, and drawing conclusions or verification. The results of the research show (1) The application of the Islamic Teachers College curriculum in improving students' speaking skills at the Darul Fikri Islamic Boarding School Ponorogo is very useful, especially for learning processes that use Arabic in directing and teaching Arabic language lessons according to Arabic language rules to improve class students' speaking skills. one Experimental. (2) Supporting and inhibiting factors: Supporting factors: The teacher's ability to teach is very important, and the learning methods used at the Darul Fikri Islamic Boarding School, Ponorogo, can support the process of implementing the Islamic Teachers College curriculum in improving speaking skills. Skills of first-year experimental students. According to the background, the inhibiting factors are. The ability of students who do not graduate from the Islamic Institute to receive Arabic language lessons and the ability of students who have difficulty accepting the subjects taught. (3) The effect of implementing the Islamic Teachers College curriculum is that students can use Arabic in communicating within the Islamic Institute, both actively and passively, per the correct Arabic language rules.